Influence of Selected Vehicle Maneuvers on Reduction of the Urban Roads Capacity - Jan Celko; Matus Kovac; Kristina Huszarova (Communications - Scientific letters of the University of Zilina, 2019)
Capacity assessment of urban roads according to Slovak standard does not sufficiently take into account the influence of vehicle maneuvers on road section performance between the two intersections. This research analyzed turning relations on selected urban road intersections and the influence of right turn and left turn on major stream speed changes. For the purpose of determining the influence of the right turn on decrease in capacity, measurements were carried out at 7 uncontrolled intersections with curve radius ranging from 6 to 30m. To determine the influence of the left turn on the capacity of urban road a critical gap was evaluated, using the Raff’s, method, based on the analysis of accepted and rejected gaps in the major traffic stream, which was one of the main inputs for simulations. The findings were used to determine the influence of selected maneuvers on the road capacity, which led to a proposal for reduction coefficients based on computational analysis performed using simulations in PTV VISSIM.